Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1096/fj.201801349rr
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E 2 secreted by mesenchymal stem cells protects against acute liver failure via enhancing hepatocyte proliferation

Abstract: Bone marrow–derived mesenchymal stem cells (MSCs) have been recently used in clinical trials as treatment for liver diseases. However, the underlying mechanism of their effectiveness remains largely unexplored. In the present study, we confirmed that the protective effects of MSCs on mouse model of acute liver failure (ALF) were based on MSC‐secreted prostaglandin (PG)E2. Our data confirmed that MSC‐secreted PGE2 not only inhibited apoptosis but also enhanced hepatocyte proliferation, thus attenuating ALF. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 35 publications
(40 reference statements)
2
39
0
Order By: Relevance
“…Paralyzed with our previous study 13 , MSC protected against ALF through PGE 2 , as revealed by plasma levels of ALT and AST ( Figure 1A) and liver damage in HE staining ( Figure 1B). TUNEL and PI staining con rmed the hepatocyte necrosis and apoptosis was decreased when MSC infusion, especially in MSC-COX2(+) group, however, MSC-COX2(-) failed to decrease hepatocyte necrosis and apoptosis ( Figure 1C and 1D).…”
Section: Msc Protects Against Alf Via Pgesupporting
confidence: 85%
See 4 more Smart Citations
“…Paralyzed with our previous study 13 , MSC protected against ALF through PGE 2 , as revealed by plasma levels of ALT and AST ( Figure 1A) and liver damage in HE staining ( Figure 1B). TUNEL and PI staining con rmed the hepatocyte necrosis and apoptosis was decreased when MSC infusion, especially in MSC-COX2(+) group, however, MSC-COX2(-) failed to decrease hepatocyte necrosis and apoptosis ( Figure 1C and 1D).…”
Section: Msc Protects Against Alf Via Pgesupporting
confidence: 85%
“…MSC were isolated from 4-to 6-week-old C57BL/6 mice as our previous described 13 . To deplete or overexpress COX2 in MSC to inhibit or increase the synthesis and secretion of PGE 2 , the short hairpin RNA against COX2 or COX2 gene lentivirus (GeneChem, Shanghai, China) was transfected to MSCs following the manufacturer's instructions [named MSC-COX2(-) and MSC-COX2(+)].…”
Section: Isolation Of Mouse Bone Marrow Mscmentioning
confidence: 99%
See 3 more Smart Citations